Simple Device For Facilitating Surgical Illumination - et. al., Omkar Joshi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Ergonomic problems associated with illumination systems in various medical applications including surgeries, dentistry and other diagnostic processes have been the subject of concern for medical professionals. These problems include difficulties in finding a well-lit wound, time to time adjustment of light, illumination intensity, generation of heat and interruption due to formation of shadows etc. Therefore, there is need for improvement in illumination system with major focus on minimizing the need and efforts for repositioning the luminaire. Present work provides user friendly, efficient and greener surgical illumination device. The designed prototype for better illumination provides direct, shadow-less illumination with its proper sterilization using ethylene oxide sterilization. The designed prototype is better used over the gloves as it provides proper intensity and less diffusivity. There are different prototypes designed for different applications including normal illumination ring, illumination ring with a shaft movement of light, a ring with adjustable light intensity etc. The cell viability assay showed no significant impact of light on cells and tissues.